PENGARUH KUALITAS DAN DOSIS SERESAH TERHADAP POTENSIAL NITRIFIKASI TANAH DAN HASIL JAGUNG MANIS - Purwanto Purwanto; Sri Hartati; Siti Istiqomah (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2014)
Title : EFFECT OF LITTER QUALITY  AND DOSAGE TO  POTENTIAL NITRIFICATION IN SOIL AND YIELD OF SWEET CORN. Nitrification is conversion of NH4+ to NO2¬- and NO3- by specialized bacteria. The process is very harmful to the plant, therefore should be controlling nitrification in the soil with the application of litter. The purpose of this study is to know the effective of litter quality and dose to control potential nitrification in the soil, and optimum for sweet corn cultivation. This research used a Randomized Block Design (RAKL) with two factor, the first is quality of litter (teak, kirinyu and a combination (teak and kirinyu) and second is the dose (5 Mg / ha, 12.5 Mg / ha and 20 Mg / ha). The results showed that the interaction of quality and dose significantly affect to soil nitrification potential at 2nd and 10th week. Application of kirinyu litter with high quality and doses of 20 Mg / ha had the highest concentration of NO2-, while the application of mix litter with middle quality and dose of 12.5 Mg / ha were lowest concentration of NO2-. Nitrification potential was not significantly correlated with crop yields. Litter kirinyu with high quality and dose of 20 Mg / ha is expected optimum to be applied in the cultivation of sweet corn.